(3CKQ bjeI GdYdGeI GdJLGQjI Ydi GdhdGA ddYdGeI GdJLGQjI (B: s (3OQGSI ejOGfjI HGdJWHjb Ydi Hfc eUQ (B/ s - (3eMeO YHOGdaVjd gdGds; (3gTGe SjO SdjeGf YHOGddg (B: s ((3GdbGgQI (B: s (3eMeO YHOGdaVjd gdGd (B: s, 2018)
(3jgOa GdHMK Gdi GdJCUjd GdfXQi dcdG ef(B: (3bjeI GdYdGeI GdJLGQjI h GdhdGA ddYdGeI GdJLGQjI h eYQaI bjeI GdYdGeI GdJLGQjI h CHYGOgG GdeNJdaI Ydi GdhdGA ddYdGeI GdJLGQjI(B. (3ceG jgOa GdHMK CjVG Gdi GdJYQa Ydi JCKjQ GdYhGed GdOjehLQGajI (B((3GdSf (B- (3GdfhY (B- (3GdeDgd GdJYdjei(B) (3Ydi GdhdGA ddYdGeI GdJLGQjI(B. (3h CNjQG jgOa GdHMK Gdi hVY fehPL hUai ebJQM dbjGS JCKjQ bjeI GdYdGeI GdJLGQjI Ydi GdhdGA ddYdGeI GdJLGQjI dHfc eUQ(B. (3h cGfJ eJZjQGJ GdHMK gi bjeI GdYdGeI GdJLGQjI ceJZjQ eSJbd h CHYGOgG gi(B: (3GdLhOI GdeOQcI ddYdGeI GdJLGQjI(B: (3h GdhYi HGdYdGeI GdJLGQjI(B: (3h GdUhQI GdPgfjI ddYdGeI GdJLGQjI h GdGQJHGWGJ HGdYdGeI GdJLGQjI h GdeJZjQ GdCNQ gh GdhdGg ddYdGeI GdJLGQjI h gh GdeJZjQ GdJGHY(B. (3h Je GdJWHjb Ydi YjfI YThGFjI efJXeI ef YedGA Hfc eUQ HGSJNOGe GSdhH GdebGHdGJ GdTNUjI dLeY GdHjGfGJ HGSJNOGe bGFeI GSJbUGA h JMdjd fJGFL GdGSJLGHGJ HGSJNOGe HQfGeL (B((3SHSS(B) (3h bO Je GdJMdjd HGSJNOGe GdEMUGA GdhUai h GdEMUGA GdJMdjdi eKd GNJHGQ GdKHGJ h GdUOb h GNJHGQ GdGQJHGW Hjf GdeJZjQGJ h eYGed GdGfMOGQ GdHSjWs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdJLGQI (B- (3bSe GOGQI GdCYeGds
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdYdGeI GdJLGQjI s; (3GdhdGA ddYdGeI GdJLGQjI s; (3Hfc eUQ s